Online assessment literacy level of EFL teachers in Denpasar - Putra, I Kadek Krisna Dharma; Paramartha, A.A. Gede Yudha; Mahayanti, Ni Wayan Surya (Research and Social Study Institute, 2024)
This study explored the online assessment literacy (OAL) of teachers in Denpasar, focusing on categorical variables affecting literacy levels. Utilizing a descriptive quantitative approach, the research used a cross-sectional design. The population was composed of EFL teachers within the Denpasar region, data were collected from elementary to high school teachers through scored survey questionnaires. Samples were 64 EFL teachers composed of diverse demographic backgrounds. Findings indicated a predominant